Optimal, Integral, Likely Optimization, Integral Calculus, and Probability for Students of Commerce and the Social Sciences - Belevan, Bruno; Hamidi, Parham; Malhotra, Nisha; Yeager, Elyse (Open textbook library., 2020)
Optimal, Integral, Likely is a free, open-source textbook intended for UBC’s course MATH 105: Integral Calculus with Applications to Commerce and Social Sciences. It is shared under the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License.